Delivery of Health-Related Information to Rural Practitioners - Kabler, Anne W. (1981)
A program to develop library resources was instituted in eight hospitals and one ambulatory care facility in the rural low country of South Carolina from July 1978 to July 1979. The program's goal was to increase availability and awareness of informational resources and their value in the continuing and in-service education of health personnel. This paper reports on the program's inception, components, evaluation, success, and implications for similar programs.